STOCK STATUS OF BLUE SWIMMING CRAB (Portunus pelagicus) IN TANAH LAUT, SOUTH KALIMANTAN, AND ITS ADJACENT WATERS - Ali Suman; Ap'idatul Hasanah; Andina Ramadhani Putri Pane; Pratiwi Lestari (Indonesian Fisheries Research Journal, 2020)
A study on the stock status of blue swimming crab (Portunus pelagicus Linnaeus, 1758) was conducted in Tanah Laut, South Kalimantan waters, based on data collected in March to November 2017. The results showed that the growth pattern of blue swimming crab in Tanah Laut waters was negatively allometric and the sex ratio of males to females was 1.0 : 1.7. The chi-square test indicated that the total males and total females of the blue swimming crab was significantly different. It means that there was an imbalance in numbers between males and females. The estimated length at first capture (Lc) was 127.26 mm (carapace width; CW), smaller than the length at first maturity (Lm) at 133.24 mmCW. The growth parameter of blue swimming crab was 1.1year with a maximum carapace width (L) of 204.3 mmCW. The estimated instantaneous total mortality (Z) and natural mortality (M) were 3.04/year and 1.24/year, respectively. While fishing mortality (F) and exploitation rate (E) were 1.80/year and 0.59/year, respectively, the estimated spawning potential ratio (SPR) was 11.1 %. Therefore, the stock status was categorized as overfishing. In order to ensure the sustainability of the blue swimming crab, a precautionary approach,, such as reducing fishing effort by 18 % of the current situation, is strongly recommended to apply.